High Responsivity of Sol-gel TiO2NPs/Si Photodetectors Deposited by Spin Coating Method - Ahmed Kurda; Shaida Kakil; Yousif Hassan (Polytechnic Journal)
This study used the sol-gel spin coating process to generate a thin film of titanium dioxide nanoparticles (TiO2NPs) on silicon substrates for photodetectors. This method is simple, fast, cost-effective, ecologically friendly, and appropriate for large-scale manufacturing. The size, shape, crystal structure, and optical and electrical characteristics of the produced nanoparticles were investigated using high-resolution transmission electron microscopy (HR-TEM), X-ray diffraction, UV-VIS spectroscopy, and Hall effect measurements. The data show that the particles are 15e20 nm in size and exhibit the anatase crystallite phase of titanium dioxide. The optical measurements revealed that the TiO2NPs generated on the glass substrate had an optical energy band gap of 3.35 eV. The Hall Effect measurements showed that the generated films were n-type. TiO2NPs/Si heterojunction exhibited diode-like rectifying IeV characteristics in dark and light conditions. The ideality factor exceeded two, and the rectification factor for TiO2NPs/Si was 32.0891. The photoelectric capabilities of the produced photodetectors were evaluated using a bias voltage of 1 volt. According to the currentevoltage curve, a photodetector of anatase TiO2NPs/Si heterojunction exhibits a high responsivity of 6 A/W at 375 nm and 70.225 A/W at 545 nm. Additionally, it has an incident photon-to-current conversion efficiency (IPCE) of 6.0% at 370 nm and 12.8% at 565 nm.